Implementation of the Direct Cash Assistance Policy in Pasir Jati Urban Village, Ujung Berung Sub-District, Bandung City - Hidayat, Aldi; Muhammad Ridwan Caesar; Fadlan Abdillah Salam (GoResearch - Research & Publishing House, 2025)
This research is motivated by the allegation that the policy implementation of the Direct Cash Assistance in Pasir Jati Village is still not optimal, one of the problems that occurs is the lack of information and socialization to the community. This study aims to analyze the implementation of the Direct Cash Assistance policy in Pasir Jati Village, Ujung Berung Subdistrict, Bandung City. This research uses the theory of Edward III with indicators: communication, resources, disposition and bureaucracy. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of Direct Cash Assistance in Pasir Jati Village has been running quite well, but still faces various obstacles, such as lack of coordination between agencies, inaccurate targeting of recipients, and lack of adequate human resources. To overcome these obstacles, the research suggests improving communication and coordination between related parties and increasing the capacity of human resources at the kelurahan level.